2012
DOI: 10.1177/0961203312444495
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for advanced glycation end products (RAGE) polymorphisms are associated with systemic lupus erythematosus and disease severity in lupus nephritis

Abstract: RAGE polymorphisms are associated with susceptibility to SLE and LN. In addition, some of these polymorphisms are likely to be associated with disease severity and initial response to treatment in LN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 44 publications
1
40
1
Order By: Relevance
“…The -429T/C and -374T/A polymorphisms were shown to have a marked effect on the transcriptional activity (Hudson et al, 2001), and the G82S polymorphism occurring in the AGE-binding domain has been shown to have an enhanced binding and cytokine/MMP generation following ligation by a prototypic S100/calgranulin (Hofmann et al, 2002). The associations identified between RAGE polymorphisms and diseases have primarily focused on inflammatory complications such as Crohn's disease, systemic lupus erythematosus, and cardiovascular diseases (Peng et al, 2009;Dabritz et al, 2011;Lu et al, 2011;Martens et al, 2012). However, whether these polymorphisms are associated with the development of COPD has not been studied.…”
Section: Introductionmentioning
confidence: 97%
“…The -429T/C and -374T/A polymorphisms were shown to have a marked effect on the transcriptional activity (Hudson et al, 2001), and the G82S polymorphism occurring in the AGE-binding domain has been shown to have an enhanced binding and cytokine/MMP generation following ligation by a prototypic S100/calgranulin (Hofmann et al, 2002). The associations identified between RAGE polymorphisms and diseases have primarily focused on inflammatory complications such as Crohn's disease, systemic lupus erythematosus, and cardiovascular diseases (Peng et al, 2009;Dabritz et al, 2011;Lu et al, 2011;Martens et al, 2012). However, whether these polymorphisms are associated with the development of COPD has not been studied.…”
Section: Introductionmentioning
confidence: 97%
“…The −429 T/C and −374 T/A polymorphisms have been shown to exert significant effects on the transcriptional activity [13], and the G82S polymorphism, which occurs in the AGE binding domain, has been shown to have an enhanced ligand-binding affinity and leads to the increased ligand-stimulated activation of proinflammatory mediators [14]. The functional polymorphisms of the RAGE gene have been studied for their associations with various diseases, including Crohn's disease, systemic lupus erythematosus, Alzheimer's disease, multiple sclerosis, and cardiovascular diseases [1520]. However, the association between the RAGE polymorphisms and AAA has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Abdulahad et al [58] have reported that urinary HMGB-1 produces disease activity in patients with lupus nephritis. Interestingly, Martens et al [59] have found that some RAGE polymorphism is linked to the susceptibility to SLE and lupus nephritis. These data support the concept that RAGE might play an important role in the pathogenesis of SLE and its related renal complications by mediating the inflammatory responses in the kidney via the interaction with HMGB-1.…”
Section: Receptor For Advanced Glycation Endproducts and Lupus Nephritismentioning
confidence: 97%